Static and impact response of a single-span stone masonry arch - Pulatsu, Bora (2021)
Unreinforced masonry structures are susceptible to man-made hazards such as impact and blast loading. However, the literature on this subject mainly focuses on masonry wall behavior, and there is a knowledge gap about the behavior of masonry arches under high-strain loading. In this context, this research aims to investigate both quasistatic and impact response of a dry-joint stone masonry arch using the discrete element method. Rigid blocks with noncohesive joint models are adopted to simulate dry-joint assemblages. First, the employed modeling strategy is validated utilizing the available experimental findings, and then sensitivity analyses are performed for both static and impact loading, considering the effect of joint friction angle, contact stiffness, and damping parameters. The outcomes of this research strengthen the existing knowledge in the literature regarding the computational modeling of masonry structures that are subjected to usual and extreme loading conditions. The results highlight that applied discontinuum-based numerical models are more sensitive to stiffness parameters in high-strain loading than static analysis.